Orthomnion javense (Mniaceae), a formerly Malesian species newly confirmed for China and new to Laos, with O. loheri as a new synonym - Yi, Yan-Jun; He, Si (Phytotaxa, 2014)
We evaluated the taxonomic status of Orthomnion javense and O. loheri based on morphological characteristics. The primary distinction between the two species on the basis of the leaf border differentiation does not uphold with a prudent examination of Chinese and other Asian specimens. Orthomnion loheri is a new synonym of O. javense, a formerly Malesian species which is newly confirmed for China and is here reported new to Laos. The previously reports of Plagiomnium elimbatum in China were based on some misidentifications of O. javense, and the former is excluded from the Chinese moss flora.